Effect of Five Elements Music Concrete Hypnosis Technique on Subthreshold Depression after Stroke - ZHANG Jiale; ZHOU Xia; LIU Jianxian; QIAN Qian; WANG Qin; WANG Zhensong (康复学报)
ObjectiveTo observe the effect of five elements music concrete hypnosis technique on depressive mood state, somatic motor function and activities of daily living of patients with subthreshold depression after stroke.MethodsA total of 78 patients with subthreshold depression after stroke in the Second Affiliated Hospital of Shandong University of Traditional Chinese Medicine were randomly divided into control group and observation group, with 39 cases in each group. During the treatment,a total of 3, 1 case fell off/stopped in the control group and the observation group respectively. Finally, a total of 36,38 cases were included in the control group and the observation group respectively. The control group received individualized emotional support from medical staff with no professional psychological training an conventional treatment. The observation group received five elements music concrete hypnosis technique intervention on the basis of conventional treatment. The hypnotic relaxation and movement guidance language in the background of Jue tune of five element music were recorded by professional psychological technicians, and the patients received motor imagination training in the music background under the guidance of therapists. Both groups were treated for 30 minutes a time, once a day, six times a week, lasting for four weeks. Before treatment and four weeks after treatment, the Hamilton depression scale 17 (HAMD-17) and the center for epidemiologic studies depression scale (CES-D) were used to evaluate the depressive mood state of patients; the Fugl-Meyer assessment (FMA) was used to evaluate somatic motor function; the modified Barthel index (MBI) scale was used to evaluate the ability of activities of daily living. In addition, 12 patients in the observation group underwent resting-state functional magnetic resonance imaging (rs-fMRI) to observe the activation range of brain regions.ResultsCompared with those before treatment, the scores of HAMD-17 and CES-D of both groups decreased significantly after treatment, and the scores of FMA and MBI increased significantly (P<0.05). Compared with the control group, the scores of HAMD-17 and CES-D of the observation group decreased significantly after treatment, and the scores of FMA and MBI increased significantly (P<0.05). Compared with those before treatment, the occipital visual cortex, posterior cingulate, cortical area and other peripheral brain areas (Brodman zone 18, 30, 31) in the observation group were activated after treatment.ConclusionFive elements music concrete hypnosis technique can effectively improve the depressive mood state, somatic motor function and ability of activities of daily living of patients with subthreshold depression after stroke, which may be related to the activation of occipital visual cortex, posterior cingulate and cortical areas.